The gifts of imperfection ebook Let go of who you think you're supposed to be and embrace who you are. - Brown, Brené (2022)
NEW YORK TIMES BESTSELLER This tenth-anniversary edition of the game-changing #1 New York Times bestseller features a new foreword and new tools to make the work your own. For over a decade, Brené Brown has found a special place in our hearts as a gifted mapmaker and a fellow traveler. She is both a social scientist and a kitchen-table friend whom you can always count on to tell the truth, make you laugh, and, on occasion, cry with you. And what's now become a movement all started with The Gifts of Imperfection , which has sold more than two million copies in thirty-five different languages across the globe. What transforms this book from words on a page to effective daily practices are the ten guideposts to wholehearted living. The guideposts not only help us understand the practices that will allow us to change our lives and families, they also walk us through the unattainable and sabotaging expectations that get in the way. Brené writes, "This book is an invitation to join a wholehearted revolution. A small, quiet, grassroots movement that starts with each of us saying, 'My story matters because I matter.' Revolution might sound a little dramatic, but in this world, choosing authenticity and worthiness is an absolute act of resistance."